73.9k views
5 votes
Keri is simplifying 5·10^−3.

1. Which could be the first step to use when simplifying the expression?
A) 5 · 10^−3 = 5(10)^1/3
B) 5 · 10^-3 = 1/50^3
C) 5 · 10^−3 = 1/50^1/3
D) 5 · 10^−3 = 5(1/10^3)



2. Which is equivalent to
8/10^2?
A) 800
B) 1/80
C) 80
D) 100/8

Keri is simplifying 5·10^−3. 1. Which could be the first step to use when simplifying-example-1
User Matt Usher
by
6.7k points

2 Answers

5 votes

Answer:

d then a

Explanation:

User Midnight Guest
by
6.6k points
1 vote

Answer:

1. D

2. A

Explanation:

Q1. Kerry is simplifying
5\cdot 10^(-3)

By the definition of negative powers,


a^(-n)=(1)/(a^n)

Hence,


10^(-3)=(1)/(10^3)

So, the first step in simplifying the expression is


5\cdot 10^(-3)=5\cdot (1)/(10^3)

Q2. Given the expression


(8)/(10^(-2))

First, use the definition of negative powers:


10^(-2)=(1)/(10^2)

Thus,


(8)/(10^-2)=(8)/((1)/(10^2))=8\cdot 10^2=8\cdot 100=800

User Algorhythm
by
5.3k points